Governor's Residence, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A painting of the Governor's Residence surrounded by the tropical flora of the Botanical Gardens, the flag of the United Kingdom at full mast and the green St. Ann's hills filling the background. When Trinidad and Tobago became a republic in 1976, this house became "The President's House" - the residence of the President of the Republic of Trinidad and Tobago.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Flags--Great Britain; Architecture--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The